PERANCANGAN GALERI SENI KERAJINAN KABUPATEN SINTANG DENGAN PENDEKATAN NEO-VERNAKULAR - Laura Karina; Uray Fery Andi; Tri Wibowo Caesariadi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The typical handicrafts of Sintang Regency have been known worldwide and have been registered by UNESCO as an Intangible Cultural Heritage. The handicrafts that are quite famous for being typical handicrafts of Sintang Regency are Dayak Ikat Woven, Bead Embroidery, and Rattan Weaving. The current problem is the lack of adequate facilities for craftsmen in marketing, exhibiting, and introducing handicrafts so that the development of the creative economy is slow. The purpose of designing the Art Craft Gallery is as a place for production, exhibitions, and buying and selling activities for handicrafts typical of Sintang Regency by applying traditional architectural forms through a Neo-Vernacular design approach. The design uses the J.C. Jones, which contains ideas, information, and analysis, synthesis, evaluation, and optimization. Located on Jl. Sintang-Putussibau, Kelam Permai District, Sintang Regency, the design consists of many mass buildings with the main function being the Art Craft Gallery as an exhibition place and the art market as a place for buying and selling, supporting functions in the form of a multipurpose hall, studio workshop, plaza, and cafeteria. Supporting functions accommodate service activities such as prayer rooms, lavatory, and management areas. Through the Neo-Vernacular approach, the main building design refers to the Betang Ensaid Panjang House as a concept of traditionality which is applied through the shape of the building, the provision of Dayak motifs, to the outer and inner layout with a symmetrical pattern such as the Neo-Vernacular design principle.